Religious Contestation in Rural Area Cigugur Kuningan West Java, Indonesia - Aripudin, Acep (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2020)
Religious harmony has become a fundamental challenge in a pluralistic society like Indonesia. Although this diversity has in many ways created space for cooperation, interfaith competition remains open and prone to conflict. This article discusses religious competition at the foot of Mount Ciremai, a small town in Kuningan, West Java, among Islam, Catholic and Madraism (a local syncretic religious stream). This research is a qualitative descriptive study. The study finds out that the competition began since early 20th century. This happened in order to maintain the existence and religious identity of each group. However, these tensions have recently begun to melt away and a space for dialogue and cooperation between adherents of the three religions and beliefs has begun to develop. Several factors that influence this change include the openness of each adherent, interfaith marriage, and political aspirations.